GAYA KEPEMIMPINAN CAMAT KINOVARO KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Suharjo, Suharjo; Hattab, Syahrudin; Anna, Hajar (Katalogis, 2021)
The purpose of this study was to find out the Leadership Style of the Kinovaro Sub-District of Sigi District, Central Sulawesi Province. The main theory that becomes the reference in this study is the theory of Luthans Leadership Style (2005: 649) by looking at two three aspects, namely leader-member relations, Task Structures, Power and Leaders (Leader's Position). . Qualitative Research Methods. The location of this study in this study was carried out in the Kinivaro Sub-District Office in Sigi Regency, Central Sulawesi Province, with 6 informants selected purposively. Data collection is done by conducting interviews, observation, and documentation. Data analysis techniques use the Interactive model of Miles and Huberman. Based on the results of the research of the leadership style of the District Head of Kinivaro District of Sigi, it can be concluded that of the three aspects, namely leader-member relations, Task Structures, Power and Leaders (Leaders' Position) as a whole can be implemented well , except that the dominant one is the leadership style that is oriented towards the task.